An artificial graphite negative electrode material and its preparation method and application
By mixing petroleum coke and asphalt and then carbonizing and graphitizing, cost-effective artificial graphite negative electrode materials are prepared, which solves the problems of low energy density and high production cost of lithium-ion battery negative electrode materials, and improves battery capacity and cycle life.
Patent Information
- Application Number
- CN202211650397.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-21
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2042-12-21
AI Technical Summary
The negative electrode materials of lithium-ion batteries have problems such as low energy density, slow charging speed, low battery capacity and high production costs, which limit their application and development in various fields.
By mixing petroleum coke and asphalt and then granulating, the first and second graphitization materials are prepared and mixed, and the cost-effective artificial graphite negative electrode material is prepared.
It significantly improves battery capacity and energy density, improves cycle life, and reduces production costs, making it cost-effective.
Smart Images

Figure BDA0004010280260000111 
Figure BDA0004010280260000121
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to an artificial graphite negative electrode material and a preparation method and application thereof. Background Art
[0002] As the demand for new energy vehicles continues to increase, lithium-ion batteries, as an important component, have attracted much attention. Lithium-ion batteries are currently widely used new energy storage and conversion devices, with advantages such as high storage energy density, long cycle life and environmental friendliness.
[0003] The negative electrode material of lithium-ion batteries is one of the key factors that determine the overall electrochemical performance of the battery. Among them, low energy density, slow charging speed, low battery capacity, and high production cost are the main problems that limit its application and development in various fields.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] The first purpose of the present invention is to provide a method for preparing an artificial graphite negative electrode material. By mixing a first graphitized material obtained by a specific raw material and a specific preparation method with a second graphitized material, a cost-effective artificial graphite negative electrode material is obtained, which has the advantages of high specific capacity, high energy density and good cycle performance.
[0006] The second object of the present invention is to provide an artificial graphite negative electrode material, which has the advantages of high cost performance, high specific capacity, high energy density and good cycle performance.
[0007] A third object of the present invention is to provide a lithium ion battery.
[0008] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0009] The present invention provides a method for preparing an artificial graphite negative electrode material, comprising the following steps:
[0010] The petroleum coke and asphalt are uniformly mixed and granulated to obtain a granulated material; the granulated material is carbonized to obtain a carbonized material; the carbonized material is graphitized to obtain a first graphitized material;
[0011] Wherein, the volatile matter of the petroleum coke is ≥12%;
[0012] After graphitizing the needle coke, a second graphitized material is obtained;
[0013] Wherein, the volatile matter of the needle coke is ≤8%;
[0014] After the first graphitized material and the second graphitized material are evenly mixed, the artificial graphite negative electrode material is obtained.
[0015] Preferably, the mass ratio of the first graphitized material to the second graphitized material is 50-90:10-50.
[0016] Preferably, the D of the petroleum coke 50 Particle size is 8-15 μm;
[0017] Preferably, the D of the asphalt 50 Particle size is 2 to 6 μm;
[0018] Preferably, the mass ratio of the petroleum coke to the asphalt is 85-99:1-15.
[0019] Preferably, the granulation temperature is 300-800°C, and the granulation time is 3-12h;
[0020] Preferably, the carbonization temperature is 600-1500°C, and the carbonization time is 5-15h;
[0021] Preferably, the temperature of the graphitization treatment of the carbonized material is 2500-3200° C., and the time of the graphitization treatment of the carbonized material is 6-18 hours.
[0022] Preferably, the D of the needle coke 50 The particle size is 6 to 12 μm.
[0023] Preferably, the temperature of the graphitization treatment of the needle coke is 2600-3100° C., and the time of the graphitization treatment of the needle coke is 6-18 hours.
[0024] Preferably, before the first graphitized material and the second graphitized material are uniformly mixed, the method further comprises the steps of screening and demagnetizing the first graphitized material and the second graphitized material.
[0025] The present invention also provides an artificial graphite negative electrode material, which is mainly prepared by the method for preparing the artificial graphite negative electrode material as described above.
[0026] Preferably, the artificial graphite negative electrode material has a first charge specific capacity of ≥355 mAh / g at 0.1 C, and a first charge efficiency of ≥94%.
[0027] The present invention also provides a lithium ion battery, comprising the artificial graphite negative electrode material as described above.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] (1) The method for preparing the artificial graphite negative electrode material provided by the present invention adopts specific raw materials and specific methods to prepare the first graphitized material and the second graphitized material, and mixes the two materials evenly, which can effectively combine the advantages of the two materials, significantly improve the battery capacity, effectively increase the energy density, greatly improve the cycle life, and have a very high cost performance.
[0030] (2) The method for preparing the artificial graphite negative electrode material provided by the present invention has the advantages of being simple, easy to operate, having low raw material cost, and being suitable for mass production.
[0031] (3) The artificial graphite negative electrode material provided by the present invention has the advantages of low cost, high capacity, long service life, and high cost performance, among which the first charge specific capacity at 0.1C can reach more than 355 mAh / g, and the first charge efficiency is more than 94%. DETAILED DESCRIPTION
[0032] The technical scheme of the present invention will be clearly and completely described below in conjunction with specific embodiments, but it will be appreciated by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work, all belong to the scope of protection of the present invention. If specific conditions are not indicated in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0033] In a first aspect, the present invention provides a method for preparing an artificial graphite negative electrode material, comprising the following steps:
[0034] The petroleum coke and asphalt are uniformly mixed and granulated to obtain a granulated material; the granulated material is carbonized to obtain a carbonized material; the carbonized material is graphitized to obtain a first graphitized material.
[0035] Wherein, the volatile matter of the petroleum coke is ≥12%, including but not limited to any point value of 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20% or the range value between any two of them, preferably 12% to 15%.
[0036] Among them, petroleum coke is used as the raw material for preparing artificial graphite, and asphalt is used as a binder to coat the surface of the asphalt and make the particles bond to each other.
[0037] The present invention can increase the particle size of petroleum coke, reduce its specific surface area, improve structural stability, and further improve its cycle performance in lithium ion batteries by granulating petroleum coke.
[0038] After the needle coke is graphitized, a second graphitized material is obtained.
[0039] Since the specific capacity of needle coke decreases after granulation and granulation of needle coke increases the production cost, the needle coke is not granulated in the present invention.
[0040] The volatile matter of the needle coke is ≤8%, including but not limited to any one of 8%, 7%, 6%, 5%, 4%, and 3% or a range between any two of them, preferably 5% to 8%.
[0041] After the first graphitized material and the second graphitized material are evenly mixed, the artificial graphite negative electrode material is obtained.
[0042] The present invention uses specific raw materials and specific methods to prepare the first graphitized material and the second graphitized material, and mixes the two materials uniformly, which can effectively combine the advantages of the two materials. Compared with the original single graphite material, the battery capacity can be significantly improved, the energy density is effectively increased, and the cycle life is greatly improved. Compared with the single graphite product, the present invention has a very high cost performance. It solves the problems of high production cost and low battery capacity existing in the current negative electrode materials of lithium ion batteries.
[0043] Specifically, using petroleum coke as raw material to prepare the first graphitized material can significantly improve the structural stability of the artificial graphite negative electrode material, thereby improving its cycle performance and reducing production costs; using needle coke as raw material to prepare the second graphitized material can significantly improve the specific capacity of the artificial graphite negative electrode material.
[0044] In addition, the preparation method is simple, easy to operate, has low raw material cost, and is suitable for mass production.
[0045] The artificial graphite negative electrode material prepared by the above method can be used to prepare negative electrode plates of lithium-ion batteries, and then assembled into lithium-ion batteries, which have excellent electrochemical properties.
[0046] Preferably, the mass ratio of the first graphitized material to the second graphitized material is 50-90 (including but not limited to any one of 55, 60, 65, 70, 75, 80, 85 or a range between any two): 10-50 (including but not limited to any one of 15, 20, 25, 30, 35, 40, 45 or a range between any two).
[0047] In some specific embodiments of the present invention, the ratio of the mass of the second graphitized material to the sum of the mass of the first graphitized material and the second graphitized material is 10% to 50%.
[0048] Preferably, the D of the petroleum coke 50The particle size is 8 to 15 μm, including but not limited to any point value of 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, and 14 μm, or a range value between any two of them.
[0049] Preferably, the D of the asphalt 50 The particle size is 2 to 6 μm, including but not limited to any point value of 3 μm, 4 μm, and 5 μm, or a range value between any two of them.
[0050] Preferably, the mass ratio of the petroleum coke to the asphalt is 85-99 (including but not limited to any one of 87, 89, 91, 93, 95, 97 or a range between any two of them): 1-15 (including but not limited to any one of 2, 4, 6, 8, 10, 12, 14 or a range between any two of them).
[0051] Among them, the amount of asphalt added determines the particle size of the finished product. Using the mass ratio within the above range can produce an artificial graphite negative electrode material with a particle size that meets the requirements.
[0052] In some specific embodiments of the present invention, the ratio of the mass of the asphalt to the sum of the mass of the petroleum coke and the asphalt is 1% to 15%.
[0053] Preferably, the granulation temperature is 300-800°C, including but not limited to any one of 400°C, 500°C, 600°C, 700°C or a range between any two of them.
[0054] The granulation time is 3 to 12 hours, including but not limited to any one of 4 hours, 6 hours, 8 hours, 10 hours, and 12 hours, or a range between any two of them.
[0055] During the granulation process, the asphalt makes the petroleum coke particles adhere to each other or coat the surface thereof to increase the particle size.
[0056] Preferably, the carbonization temperature is 600-1500°C, including but not limited to any point value of 700°C, 800°C, 900°C, 1000°C, 1100°C, 1200°C, 1300°C, 1400°C or a range between any two of them.
[0057] The carbonization time is 5 to 15 hours, including but not limited to any one of 6 hours, 8 hours, 10 hours, 12 hours, and 14 hours, or a range between any two of them.
[0058] Among them, the carbonization step can reduce the volatile matter and increase the compaction density of the finished product.
[0059] Preferably, the temperature of the graphitization treatment of the carbonized material is 2500-3200°C, including but not limited to any one of 2600°C, 2700°C, 2800°C, 2900°C, 3000°C, 3100°C or a range between any two of them.
[0060] The graphitization treatment time of the carbonized material is 6 to 18 hours, including but not limited to any one of 8 hours, 10 hours, 12 hours, 14 hours, and 16 hours, or a range between any two of them.
[0061] Among them, graphitization treatment can transform amorphous carbon into layered graphite with a regular structure.
[0062] Preferably, the D of the needle coke 50 The particle size is 6 to 12 μm, including but not limited to any point value of 7 μm, 8 μm, 9 μm, 10 μm, and 11 μm, or a range value between any two of them.
[0063] Preferably, the temperature of the graphitization treatment of the needle coke is 2600-3100°C, including but not limited to any point value of 2650°C, 2700°C, 2750°C, 2800°C, 2850°C, 2900°C, 2950°C, 3000°C, 3050°C or a range value between any two of them.
[0064] The graphitization treatment time of the needle coke is 6 to 18 hours, including but not limited to any one of 8 hours, 10 hours, 12 hours, 14 hours, and 16 hours, or a range between any two of them.
[0065] Preferably, before the first graphitized material and the second graphitized material are uniformly mixed, the method further comprises the steps of screening and demagnetizing the first graphitized material and the second graphitized material.
[0066] In some specific embodiments of the present invention, the mesh size of the sieve used for screening is 325 meshes.
[0067] In some specific embodiments of the present invention, the mixing time of the first graphitized material and the second graphitized material is 30 to 60 minutes, including but not limited to any one of 35 minutes, 40 minutes, 45 minutes, 50 minutes, and 55 minutes, or a range between any two of them.
[0068] In some specific embodiments of the present invention, the mixing is carried out in a VC mixer, including the mixing of petroleum coke and asphalt and the mixing of the first graphitized material and the second graphitized material. The granulation is carried out in a high-temperature granulation kettle. The graphitization treatment is carried out in a graphitization furnace. The screening is carried out in an ultrasonic vibration screen.
[0069] In some specific embodiments of the present invention, the petroleum coke includes sponge coke and / or honeycomb coke, but does not include needle coke.
[0070] In some specific embodiments of the present invention, the asphalt includes medium-temperature asphalt and high-temperature asphalt.
[0071] In a second aspect, the present invention provides an artificial graphite negative electrode material, which is mainly prepared by the preparation method of the artificial graphite negative electrode material as described above.
[0072] Compared with lithium ion battery negative electrode materials prepared from natural graphite and other artificial graphites, the artificial graphite negative electrode material provided by the present invention has the advantages of low cost, high capacity, long service life, high cost performance, etc.
[0073] Preferably, the first charge specific capacity of the artificial graphite negative electrode material at 0.1C is ≥355mAh / g, including but not limited to any one of 355.5mAh / g, 355.7mAh / g, 356.0mAh / g, 356.5mAh / g, 356.9mAh / g, 357mAh / g, and 358mAh / g, or a range between any two of them; the first charge efficiency is ≥94%, including but not limited to any one of 94.5%, 95.0%, 95.5%, 96%, 97%, and 98%, or a range between any two of them.
[0074] The artificial graphite negative electrode material provided by the present invention has an initial charging specific capacity of more than 355 mAh / g and an initial charging efficiency of more than 94%, which fully meets the requirements of lithium-ion batteries.
[0075] In a third aspect, the present invention provides a lithium-ion battery comprising the artificial graphite negative electrode material as described above.
[0076] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.
[0077] In order to facilitate comparison of the electrochemical properties of the artificial graphite negative electrode materials prepared in the embodiments and comparative examples, the petroleum coke used in the following embodiments and comparative examples of the present invention is Fushun petroleum coke (volatile matter is 12.33%) produced by Fushun Petrochemical Company of PetroChina, but the type of petroleum coke is not limited thereto.
[0078] In order to facilitate comparison of the electrochemical properties of the artificial graphite negative electrode materials prepared in the embodiments and comparative examples, the asphalt used in the following embodiments and comparative examples of the present invention is high-temperature asphalt (softening point is 205°C) produced by Xinjiang Zhongtan New Materials Technology Co., Ltd., but the type of asphalt is not limited to this.
[0079] In order to facilitate comparison of the electrochemical properties of the artificial graphite negative electrode materials prepared in the embodiments and comparative examples, the needle coke used in the following embodiments and comparative examples of the present invention is Yida needle coke (volatile matter is 6.57%) produced by Shandong Yida New Materials Co., Ltd., but the type of needle coke is not limited thereto.
[0080] Example 1
[0081] The method for preparing the artificial graphite negative electrode material provided in this embodiment comprises the following steps:
[0082] (1) Preparation of the first graphitized material (secondary particles of petroleum coke): a certain amount of petroleum coke is crushed and shaped into D by a mechanical grinding and classifying machine. 50 The particle size is 9 μm. A certain amount of high-temperature asphalt is crushed and shaped into D 50 The particle size is 4 μm. The crushed petroleum coke and high-temperature asphalt are mixed evenly using a VC mixer, wherein the mass ratio of petroleum coke to asphalt is 92:8. The mixed material is put into a high-temperature granulation kettle, the temperature is set to 600°C, the time is 8 hours, and granulation is performed to obtain the granulated material (i.e., granulated material).
[0083] The granulated material is carbonized at a temperature of 1100° C. for 10 hours. After the carbonization is completed, a carbonized material (ie, carbonized material) is obtained.
[0084] The carbonized material was placed in a graphitization furnace for graphitization treatment, and reacted at 3000° C. for 12 hours to obtain a first graphitized material. The first graphitized material was sieved using a 325-mesh ultrasonic vibration screen and then demagnetized.
[0085] (2) Preparation of the second graphitized material (single particle of needle coke): The needle coke is crushed and shaped to D 50 The particle size is 9 μm. Then the crushed needle coke is placed in a graphitization furnace and reacted at 3000°C for 12 hours to perform graphitization treatment to obtain a second graphitized material. The second graphitized material is sieved using a 325-mesh ultrasonic vibration screen and then demagnetized.
[0086] (3) The first graphitized material obtained in step (1) and the second graphitized material obtained in step (2) in a mass ratio of 70:30 were added to a VC mixer and mixed for 45 minutes (normal temperature). After mixing evenly, an artificial graphite negative electrode material was obtained.
[0087] Example 2
[0088] The method for preparing the artificial graphite negative electrode material provided in this embodiment comprises the following steps:
[0089] (1) Preparation of the first graphitized material (secondary particles of petroleum coke): a certain amount of petroleum coke is crushed and shaped into D by a mechanical grinding and classifying machine. 50 The particle size is 14 μm. A certain amount of high-temperature asphalt is crushed and shaped into D 50 The particle size is 2 μm. The crushed petroleum coke and high-temperature asphalt are mixed evenly using a VC mixer, wherein the mass ratio of petroleum coke to asphalt is 96:4. The mixed material is put into a high-temperature granulation kettle, the temperature is set to 800°C, the time is 4 hours, and granulation is performed to obtain the granulated material (i.e., granulated material).
[0090] The granulated material is carbonized at a temperature of 1500° C. for 5 hours. After the carbonization is completed, a carbonized material (ie, carbonized material) is obtained.
[0091] The carbonized material was placed in a graphitization furnace for graphitization treatment, and reacted at 3100° C. for 8 hours to obtain a first graphitized material. The first graphitized material was sieved using a 325-mesh ultrasonic vibration screen and then demagnetized.
[0092] (2) Preparation of the second graphitized material (single particle of needle coke): The needle coke is crushed and shaped to D 50 The particle size is 10 μm. Then the crushed needle coke is placed in a graphitization furnace and reacted at 3100°C for 8 hours to perform graphitization treatment to obtain a second graphitized material. The second graphitized material is sieved using a 325-mesh ultrasonic vibration screen and then demagnetized.
[0093] (3) The first graphitized material obtained in step (1) and the second graphitized material obtained in step (2) in a mass ratio of 50:50 were added to a VC mixer and mixed for 45 minutes (normal temperature). After mixing evenly, an artificial graphite negative electrode material was obtained.
[0094] Example 3
[0095] The method for preparing the artificial graphite negative electrode material provided in this embodiment comprises the following steps:
[0096] (1) Preparation of the first graphitized material (secondary particles of petroleum coke): a certain amount of petroleum coke is crushed and shaped into D by a mechanical grinding and classifying machine. 50 The particle size is 8μm. A certain amount of high-temperature asphalt is crushed and shaped into D 50The particle size is 6 μm. The crushed petroleum coke and high-temperature asphalt are mixed evenly using a VC mixer, wherein the mass ratio of petroleum coke to asphalt is 99:1. The mixed material is put into a high-temperature granulation kettle, the temperature is set to 400°C, the time is 12 hours, and granulation is performed to obtain the granulated material (i.e., granulated material).
[0097] The granulated material is carbonized at a temperature of 700° C. for 15 hours. After the carbonization is completed, a carbonized material (ie, carbonized material) is obtained.
[0098] The carbonized material was placed in a graphitization furnace for graphitization treatment, and reacted at 2900° C. for 16 hours to obtain a first graphitized material. The first graphitized material was sieved using a 325-mesh ultrasonic vibration screen and then demagnetized.
[0099] (2) Preparation of the second graphitized material (single particle of needle coke): The needle coke is crushed and shaped to D 50 The particle size is 7 μm. Then the crushed needle coke is placed in a graphitization furnace and reacted at 2900°C for 16 hours to perform graphitization treatment to obtain a second graphitized material. The second graphitized material is sieved using a 325-mesh ultrasonic vibration screen and then demagnetized.
[0100] (3) The first graphitized material obtained in step (1) and the second graphitized material obtained in step (2) in a mass ratio of 90:10 were added to a VC mixer and mixed for 45 minutes (normal temperature). After mixing evenly, an artificial graphite negative electrode material was obtained.
[0101] Comparative Example 1
[0102] The preparation method of the artificial graphite negative electrode material provided in this comparative example is basically the same as that in Example 1, except that in step (1), no high-temperature asphalt is added and no granulation is performed, but the petroleum coke is directly carbonized.
[0103] Comparative Example 2
[0104] The preparation method of the artificial graphite negative electrode material provided in this comparative example is basically the same as that in Example 1, except that in step (1), the granulated material is not subjected to a carbonization step, but is directly graphitized.
[0105] Comparative Example 3
[0106] The preparation method of the artificial graphite negative electrode material provided in this comparative example is basically the same as that in Example 1, except that in step (2), the needle coke is replaced by petroleum coke of the same mass.
[0107] Experimental example
[0108] The artificial graphite obtained in each embodiment and each comparative example is used as the negative electrode material, CMC and SBR are binders, and Super-P is a conductive agent. After the negative electrode material, binder and conductive agent are mixed uniformly in a mass ratio of 92:5:3, copper foil is used as the current collector for coating, and the negative electrode sheet is obtained by drying, pressing and cutting. The lithium sheet is used as the positive electrode sheet, and the electrolyte uses a mixture of 1M LiPF6 ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC), wherein the mass ratio of the three components is 1:1:1, and the separator uses PE / PP / PE composite film to assemble into a semi-button battery. Then, each battery is subjected to an electrical performance test (reference standard GB / T 38823-2020), and a constant current charge and discharge experiment is carried out at a current density of 0.1C. The charging voltage is limited to 0.005~2.0V, and the first charge specific capacity and the first charge efficiency can be obtained. The results are shown in Table 1.
[0109] Table 1 Electrical performance test results
[0110]
[0111]
[0112] As can be seen from Table 1, the 0.1C first charge specific capacity and first charge efficiency of the artificial graphite negative electrode material (i.e., Examples 1 to 3) prepared by the method provided by the present invention are better than those of the graphite product without the granulation step (Comparative Example 1) and the carbonization step (Comparative Example 2), and are higher than those of Comparative Example 3 in which the second graphitized material (single particle of needle coke) is not mixed.
[0113] It can be seen that the method for preparing the artificial graphite negative electrode material provided by the present invention, by mixing the first graphitized material and the second graphitized material, obtains high capacity while greatly improving its initial charging efficiency.
[0114] Although the present invention has been illustrated and described with specific embodiments, it should be appreciated that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents without departing from the spirit and scope of the present invention. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. Therefore, this means that all such replacements and modifications within the scope of the present invention are included in the appended claims.
Claims
1. A method for preparing an artificial graphite negative electrode material, characterized in that: The steps include: The petroleum coke and asphalt are uniformly mixed and granulated to obtain a granulated material; the granulated material is carbonized to obtain a carbonized material; the carbonized material is graphitized to obtain a first graphitized material; Wherein, the volatile matter of the petroleum coke is ≥12%; After graphitizing the needle coke, a second graphitized material is obtained; Wherein, the volatile matter of the needle coke is ≤8%; The first graphitized material and the second graphitized material are uniformly mixed to obtain the artificial graphite negative electrode material; The petroleum coke includes sponge coke and / or honeycomb coke; The artificial graphite negative electrode material prepared by the preparation method of the artificial graphite negative electrode material has a first charge specific capacity of ≥355 mAh / g at 0.1C and a first charge efficiency of ≥94%.
2. The method for preparing the artificial graphite negative electrode material according to claim 1, characterized in that: The mass ratio of the first graphitized material to the second graphitized material is 50-90:10-50.
3. The method for preparing the artificial graphite negative electrode material according to claim 1, characterized in that: The D of petroleum coke 50 Particle size is 8~15μm; and / or, the D of the asphalt 50 The particle size is 2~6μm.
4. The method for preparing the artificial graphite negative electrode material according to claim 1, characterized in that: The mass ratio of the petroleum coke to the asphalt is 85-99:1-15.
5. The method for preparing the artificial graphite negative electrode material according to claim 1, characterized in that: The granulation temperature is 300-800° C., and the granulation time is 3-12 hours.
6. The method for preparing the artificial graphite negative electrode material according to claim 1, characterized in that: The carbonization temperature is 600-1500° C., and the carbonization time is 5-15 hours.
7. The method for preparing the artificial graphite negative electrode material according to claim 1, characterized in that: The temperature of the graphitization treatment of the carbonized material is 2500-3200° C., and the time of the graphitization treatment of the carbonized material is 6-18 hours.
8. The method for preparing the artificial graphite negative electrode material according to claim 1, characterized in that: The D of the needle coke 50 The particle size is 6~12μm.
9. The method for preparing the artificial graphite negative electrode material according to claim 1, characterized in that: The temperature of the graphitization treatment of the needle coke is 2600-3100° C., and the time of the graphitization treatment of the needle coke is 6-18 hours.
10. The method for preparing the artificial graphite negative electrode material according to claim 1, characterized in that: Before the first graphitized material and the second graphitized material are uniformly mixed, the method further includes the steps of screening and demagnetizing the first graphitized material and the second graphitized material.
11. An artificial graphite negative electrode material, characterized in that: The artificial graphite negative electrode material is prepared by the preparation method of any one of claims 1 to 10.
12. A lithium ion battery, characterized in that: Comprising the artificial graphite negative electrode material according to claim 11.
Citation Information
Patent Citations
Composite graphite negative electrode material, preparation method and application thereof, and lithium ion battery
CN112661148A
Cited By
Pseudocapacitance type Nb14W3O44-x negative electrode material and preparation method and application thereof
CN116682959A